Graphene-Assisted Electrochemical Sensor for Detection of Pancreatic Cancer Markers - Xu, Zhenglei; Peng, Minsi; Zhang, Zhuliang; Zeng, Haotian; Shi, Ruiyue; Ma, Xiaoxin; Wang, Lisheng; Liao, Bihong (Frontiers in Chemistry, 2021)
Pancreatic cancer is a highly lethal gastrointestinal malignancy. Most patients are already in the middle to advanced stages of pancreatic cancer at the time of diagnosis and cannot be treated completely. As a single-atom planar two-dimensional crystal, graphene's unusual electronic structure, specific electronic properties and excellent electron transport capacity make it uniquely advantageous in the field of electrochemical sensing. In this mini-review, we summarize the potential application of graphene in pancreatic cancer detection. K-Ras gene, CEA and MicroRNA are important in the early diagnosis of pancreatic cancer.